Coping with complexity: Dealing with non-state armed actors - Yannick Deepen; Sabine Kurtenbach (German Institute of Global and Area Studies (GIGA), 2023)
Non-state armed actors (NSAAs) come in a variety of shapes and sizes, including warlordled groups, insurgencies, militias, and organised-crime syndicates to name just the most prominent examples hereof. In war or lower-level armed conflict, as well as violence-prone contexts, these groups pose acute problems for peacebuilding, democratic governance, and sustainable development. They control resources and territories, as well as compete, cooperate, or align with political and economic elites both within and beyond the state to promote the unstable status quo that serves their interests. Various challenges arise when dealing with NSAAs. Prevailing strategies vary between repression, co-optation, and submission to the rule of law. This analysis maps cross-regional trends regarding NSAAs based on available datasets. On this basis we develop a typology for NSAAs and a conceptual frame for their transformation. We then apply this to three paradigmatic case studies - Colombia, Mali, the Philippines - and formulate recommendations for the designing of improved strategies vis-à-vis development cooperation and other external actors
Keywords: 300; non-state armed actors; armed conflict; resources; violence; peacebuilding